PENGARUH TINGGI MUKA AIR GAMBUT SEBAGAI INDIKATOR PERINGATAN DINI BAHAYA KEBAKARAN DI SUNGAI JANGKANG - SUNGAI LIONG - Nur Febrianti; Kukuh Murtilaksono; Baba Barus (Indonesian National Institute of Aeronautics and Space (LAPAN), 2019)
Disasters of forest and land fires are increasingly concerned. The nature of peat soil which is easy to lose water and high organic matter content causes peat soils to be very sensitive to fire. Therefore it is necessary to know indicators for early warning of fires on peatlands. The purpose of this study is to determine the critical groundwater level (GWL) as an indicator of peatland fires on the Jangkang River - Sungai Liong. Determination of the critical point of peatland fires as a fire early warning is done by calculating the difference from the value of the undefined TMA with a range of possible errors. The TMA value is obtained from the estimation of several methods, namely data on the physical properties of the soil, the drought index, and a combination of both. The TMA estimation of the physical properties of the soil has a range of fires at depths of 74.3 - 107 cm. In estimating TMA using a drought index, potential fires occur in TMA ranging from 27 - 101 cm. While the combined estimates of the physical properties of the soil and the drought index ranged from 66.8 - 98.8 cm the occurrence of fires on peatland. The results of this study show that the estimated TMA from a combination of field data and drought index provides fairly good accuracy. Thus TMA can be an early warning indicator of the danger of peatland fires. This TMA estimation can give faster results and pretty good accuracy. But this estimation model for TMA does not necessarily apply directly to other research locations. The critical point of peat soil water depth ranges from 27 to 74 cm. The depth of the peatland surface should be maintained less than the critical point, if not then the potential for peatland fires will increase.